2021
DOI: 10.1155/2021/9117805
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Different Bacteroides vulgatus Strains against DSS-Induced Colitis

Abstract: Although the strain-dependent effects of Bacteroides vulgatus on alleviating intestinal inflammatory diseases have been demonstrated, the literature has rarely focused on the underlying causes of this effect. In this study, we selected four B. vulgatus strains (FTJS5K1, FTJS7K1, FSDTA11B14, and FSDLZ51K1) with different genomic characteristics and evaluated their protective roles against dextran sulfate sodium- (DSS-) induced colitis. Compared to the other three tested strains, B. vulgatus 7K1 more strongly am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 79 publications
4
25
0
Order By: Relevance
“…The phospholipid/cholesterol/gamma-HCH transport system of HC-enriched Bacteroides are important anti-inflammatory bacteria in the gut and could decrease cholesterol levels in the plasma and benefit health ( Yazdanyar et al., 2011 ). In this study, the decreased Phocaeicola (former name: Bacteroides ) vulgatus was worth noting, which was not only involved in the folate biosynthesis, etc., but also could fight against LPS-induced acute intestinal injury and DSS-induced colitis ( Li et al., 2021 ; Wang et al., 2022 ). After all, these are the potential risk factors of PE ( Ahmadian et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phospholipid/cholesterol/gamma-HCH transport system of HC-enriched Bacteroides are important anti-inflammatory bacteria in the gut and could decrease cholesterol levels in the plasma and benefit health ( Yazdanyar et al., 2011 ). In this study, the decreased Phocaeicola (former name: Bacteroides ) vulgatus was worth noting, which was not only involved in the folate biosynthesis, etc., but also could fight against LPS-induced acute intestinal injury and DSS-induced colitis ( Li et al., 2021 ; Wang et al., 2022 ). After all, these are the potential risk factors of PE ( Ahmadian et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mice with colitis, the abundance of Alistipes finegoldii was significantly reduced, and colitis was significantly relieved by gavage with A. finegoldii (51) (2,59,60). B. vulgatus 7K1 ameliorated DSS-induced colitis in mice by decreasing the concentrations of TNF-a and IL-6 and increasing the production of IL-10 in mouse colon tissues (12). Our data showed that B. vulgatus Bv46 treatment significantly increased the abundance of B. vulgatus in the feces of mice, and reduced the expression of colonic TNF-a, IL-6 and IL-1b.…”
Section: Discussionmentioning
confidence: 50%
“…Thus Bacteroides may be marker of gut health, and their loss may be detrimental in the setting of IBD (9). Four Bacteroides species, Bacteroides vulgatus, Bacteroides fragilis, Bacteroides ovatus and Bacteroides thetaiotaomicron, have been reported to be effective in reducing intestinal inflammatory responses (2,(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The associated risk factors of the post‐COVID‐19 syndrome may include female sex, more than five early symptoms, early dyspnea, and prior psychiatric disorders 36 . Several studies have demonstrated that Bacteroides ovatus and Bacteroides vulgatus could reduce intestinal inflammation 37 , 38 , 39 . Previous studies reported an inverse correlation of Bacteroides with fecal SARS‐CoV‐2 load and ACE2 expression 10 , 40 .…”
Section: Discussionmentioning
confidence: 99%